Modelling of outbursts and ejections occurrences during steel production - M. Malindžáková; A. Rosová; V. Baranová; J. Futó (Metalurgija, 2015)
The application of small industrial cameras linked to a computer to create models for monitoring of adverse events in the steel making process is referenced. Presented models were created by analyzing video recordings that were captured in areas that could directly threaten human life. In laboratory conditions it is possible to analyze the recorded data and then already known mathematical methods are used to evaluate phenomena that are characterized in operating conditions by rapid pace and their monitoring on site is difficult and dangerous.